Micro/nanostructured additively manufactured surfaces for enhanced flow boiling of refrigerants - Tan, Ian Chee Hean (Nanyang Technological University, 2024)
Many studies on two-phase flow boiling in microchannels involving factors that affect bubble nucleation to effectively dissipate heat from surfaces have been reported. These studies mainly involved the use of additive manufacturing fabrication orsurface modification to enhance flow boiling heat transfer performance. However, these approaches usually come with a significant amount of pressure drops, which can result in higher energy demand. In this project, a combination of additively manufactured aluminum alloys (AM AlSi10Mg) and surface modification was implemented to study the influence of microstructure on flow boiling performance and pressure drops. The experiment was conducted with R134a as the working fluid flowing through 16 parallel rectangular channels. The flow boiling performance of various samples was tested using heat flux ranging from 1.5 to 142 kW/m2 , mass flux of 73 and 146 kg/m2 ·s, and a controlled inlet subcooling temperature of 2°C. Throughout the experiment, parameters such as the average temperature of the wall, heat transfer coefficient, and pressure drop were recorded. A high speed camera was also deployed to observe the flow pattern within the cold plates. A plain conventionally manufactured aluminum (Al6061) was also fabricated and tested, and its thermal performance was compared against the AM samples. It was concluded from this experiment that the chemically etched AM surface with the refrigerant mass flux of 73 kg/m2 ·s demonstrated a significant improvement in the heat transfer coefficient by 87% at low heat flux from 1.9 to 15 kW/m2 , 70% at medium heat flux from 15 and 93 kW/m2 , and 98% at high heat flux from 93 to 140 kW/m2 as compared to plain Al6061 surface. In addition, the microstructured AM sample also exhibited at least a 33% reduction in pressure drop as compared to the plain AM surface. The etching process was able to reduce the surface roughness by removing III surface irregularities that arose during the AM fabrication process, and generated microstructures on the aluminum alloy surface. This, in turn, resulted in a significant increase in active nucleation sites to create bubbles to promote heat removal and minimize the energy required to overcome friction across the channel surfaces.